PENGARUH PENGENDALIAN INTERN TERHADAP EFEKTIVITAS PENYALURAN KREDIT PADA LEMBAGA PERKREDITAN DESA (LPD) DI KECAMATAN ABIANSEMAL KABUPATEN BADUNG - Ida Ayu Dewi Ratna Sari; Anak Agung Ayu Erna Trisnadewi (Faculty of Economics and Business, Universitas Warmadewa, 2018)
ABSTRACT This study aimed to analyze the influence of each independent variable on the dependent variable in the Village Credit Institutions (LPD) in the district of Badung regency Abiansemal. Samples used as many as 34 LPD with 68 respondents, the determination of non-probability samples using a method that is saturated samples. Data analysis technique used is multiple linear regression, which preceded the validity, reliability and classic assumption test including normality test, test multicoloniarity and heteroscedasticity test. Results of testing the hypothesis in mind that the internal control positive and significant impact on the effectiveness of lending in Village Credit Institutions (LPD) in the district of Badung regency Abiansemal either partially or simultaneously. Keywords: control environment, risk assessment, control activities, information and communication, monitoring and the effectiveness of the loan portfolio.